2010
DOI: 10.1002/agr.20241
|View full text |Cite
|
Sign up to set email alerts
|

How European consumers define the concept of traditional food: evidence from a survey in six countries

Abstract: Within the European food market, traditional food products (TFP) represent a growing segment. Nonetheless, European consumers' definition and perception of TFP have not been thoroughly addressed thus far. The specific aim of this study was to provide an all-embracing consumer definition of the concept of TFP that is comfortable for the largest possible majority of European food consumers. Cross-sectional survey data were collected from representative consumer samples from Belgium, France, Italy, Norway, Poland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 26 publications
8
72
0
4
Order By: Relevance
“…British responses are similar to what previous studies have already suggested that [105][106][107][108][109][110][111] consumers buy organic food because it is healthy, tasty, has no pesticides, and that they wish to support their local community. Surprisingly, environmental concerns were not mentioned.…”
Section: Perception Of Organic Foodsupporting
confidence: 71%
See 1 more Smart Citation
“…British responses are similar to what previous studies have already suggested that [105][106][107][108][109][110][111] consumers buy organic food because it is healthy, tasty, has no pesticides, and that they wish to support their local community. Surprisingly, environmental concerns were not mentioned.…”
Section: Perception Of Organic Foodsupporting
confidence: 71%
“…Moreover, the empirical findings of Vanhonacker et al [107] suggested that consumers perceive organic food to be the same as locally produced food. Motives of British consumers in buying organic food include fair trade, social aspects, and support of local farmers and environmental protection [6,108] as well as ethical and moral issues [109].…”
Section: Buying Organic Foodmentioning
confidence: 99%
“…FOOD- CT-2006-016264). Under the framework of the TRUEFOOD project, several articless have already been published Guerrero, Claret et al, 2009;Guerrero, Guardia et al, 2009;Ku¨hne, Vanhonacker, Gellynck, & Verbeke, 2010;Lengard, Verbeke, Vanhonacker, Naes, & Hersleth, 2010;Pieniak, Verbeke, Vanhonacker, Guerrero, & Hersleth, 2009;Vanhonacker, Lengard et al, 2010a;Vanhonacker, Verbeke et al, 2010b;Vanhonacker, Verbeke, Lengard, Guerrero, & Hersleth, 2008). Some of these publications touch upon issues that are relevant to the objectives of this study.…”
Section: Methodsmentioning
confidence: 95%
“…Consumer data regarding the growth strategies of chains are mainly available in terms of consumer attitude and acceptance of innovations in TFPs in general and in particular through expansion of product assortments. Attitudes and acceptance were strongly dependent on the type of innovation (Ku¨hne et al, 2010) and the way in which TFPs were conceptualized by individual consumers (Vanhonacker, Verbeke et al, 2010b). Tangible innovations that add value to the product without strongly modifying its traditional character were well accepted, such as improving safety or the health status of the product.…”
Section: Consumer Perceptions and Preferencesmentioning
confidence: 99%
“…Traditional foods are food made by family elders or local people on wedding or religious days [13,3. Traditional foods vary by region and tradition [21,19]. According to Vanhonacker [33], "Traditional food products are defined by European consumers as those "frequently consumed or associated with specific celebrations and / or seasons, transmitted from one generation to another, made in a specific way according to gastronomic heritage, naturally processed, and distinguished and known because of its sensory properties and associated with a certain local area, region or country" [19].…”
Section: Lıterature Revıew: 1culture Of Turkish Dessertmentioning
confidence: 99%